Response of Benthic Macrofauna to Eutrophication in a Mesocosm Experiment: Ecosystem Resilience Prevents Hypoxic Conditions - Dimitriou, Panagiotis D.; Papageorgiou, Nafsika; Karakassis, Ioannis (Frontiers in Marine Science, 2017)
A benthic-pelagic mesocosm experiment was performed for the study of the response of the benthic macrofaunal community under a eutrophication gradient. Nine mesocosms were deployed in the facilities of the Hellenic Center for Marine Research in Crete, in the eastern Mediterranean. The mesocosms were 4 m deep, contained 1.5 m3 coastal water, and included 85 liters of undisturbed sediment at the bottom. The experimental design included two eutrophication levels (Low and High) for the 58-day duration. Macrofaunal samples were collected at the end of the experiment from each mesocosm and compared to the ones collected at the beginning of the experiment from the sediment collection area. Results showed significant differences of the High eutrophication treatment in terms of macrofaunal species composition, diversity, ecological status and ecosystem processes. The increased availability of organic matter in the sediment caused differences in macrofaunal community structure by favouring deposit-feeding species with high bioturbation ability, which significantly increased their abundance. The increased bioturbation potential of the new community combined with the high organic matter consumption contributed to the oxygenation of the sediment within the mesocosm, preventing the creation of hypoxic conditions in the sediment and maintaining ecosystem health despite the highly eutrophic conditions and significant changes in sediment geochemical variables.